Efficacy of Adjuvant Chemotherapy for Stage II/III Nonsmall Cell Lung Cancer with Epidermal Growth Factor Receptor Mutations - Matsunaga, Takeshi; Takamochi, Kazuya; Hattori, Aritoshi; Fukui, Mariko; Suzuki, Kenji (The Thoracic and Cardiovascular Surgeon, 2023)
Background Adjuvant cisplatin-based chemotherapy improves the survival of patients with resected pathological stage II/III nonsmall cell lung cancer (NSCLC). However, the efficacy in patients with epidermal growth factor receptor (EGFR) mutations remains controversial.Methods This retrospective study included 353 patients with resected pathological N1/N2 stage II/III NSCLC between 2010 and 2016. Mutant EGFR (mEGFR) was detected in 76 patients. Adjuvant chemotherapy (AC) was administered to 151 patients. We compared cancer-specific survival (CSS) and recurrence-free survival (RFS) between AC and surgery-alone (SA) groups, including patients with wild-type EGFR (wEGFR) and mEGFR. Using multivariate analysis, we evaluated the prognostic factors in patients with wEGFR and mEGFR.Results The median follow-up time was 4.7 years. In patients with wEGFR, the differences in CSS and RFS between the AC (n = 114) and SA (n = 163) groups were significant (CSS: 66.8% [5 years] vs. 49.4% [5 years], p = 0.001; RFS: 54.2% [5 years] vs. 39.2% [5 years], p = 0.013). The significant prognostic factors were AC (vs. SA; p < 0.0001), diffusing capacity of the lung for carbon monoxide  > 60% (p = 0.028), tumor size (p < 0.001), lymphatic permeation (p = 0.041), and pN1 (vs. pN2; p < 0.001). However, the differences in CSS and RFS between the AC (n = 37) and SA (n = 39) groups were not significant (CSS: 64.0% [5 years] vs. 58.1% [5 years], p = 0.065; RFS: 45.0% [5 years] vs. 33.8% [5 years], p = 0.302). Multivariate analysis identified no significant prognostic factors in patients with mEGFR.Conclusion We demonstrated the efficacy of AC in patients with mEGFR and wEGFR. The efficacy of AC may be lower in patients with mEGFR than in those with wEGFR.
Keywords: lung cancer; adjuvant chemotherapy; epidermal growth factor receptor mutations